2020
DOI: 10.1038/s41598-020-76302-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhabited subsurface wet smectites in the hyperarid core of the Atacama Desert as an analog for the search for life on Mars

Abstract: The modern Martian surface is unlikely to be habitable due to its extreme aridity among other environmental factors. This is the reason why the hyperarid core of the Atacama Desert has been studied as an analog for the habitability of Mars for more than 50 years. Here we report a layer enriched in smectites located just 30 cm below the surface of the hyperarid core of the Atacama. We discovered the clay-rich layer to be wet (a phenomenon never observed before in this region), keeping a high and constant relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 129 publications
(119 reference statements)
1
23
0
Order By: Relevance
“…The positional coordinates are 24 • 03 49.6 S, 69 • 52 49.8 W (Figure 1). Note that the surrounding area has also been studied by Pfeiffer et al (2018) and Azua-Bustos et al (2020). Some of our findings are in accordance with Pfeiffer et al (2018), e.g., anhydrite polygons at the surface and needle fiber calcite in the soil profile.…”
Section: Study Site In the Hyperarid Core Of The Atacama Desertsupporting
confidence: 87%
See 2 more Smart Citations
“…The positional coordinates are 24 • 03 49.6 S, 69 • 52 49.8 W (Figure 1). Note that the surrounding area has also been studied by Pfeiffer et al (2018) and Azua-Bustos et al (2020). Some of our findings are in accordance with Pfeiffer et al (2018), e.g., anhydrite polygons at the surface and needle fiber calcite in the soil profile.…”
Section: Study Site In the Hyperarid Core Of The Atacama Desertsupporting
confidence: 87%
“…This study also highlighted the influence of soluble salts and mineralogy on water availability and likely microbial life in the deeper parts of the soil. More recently, Azua-Bustos et al (2020) found a diverse microbial community and biosignatures in humid smectite-rich subsurface layers in the hyperarid core of the Atacama Desert (at 30-40 cm depth), and Schulze-Makuch et al (2021) showed that hypolithically colonized rocks are microbial hotspots in this desert environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hotspots are characterized by hypolithic and endolithic microorganisms, as here microbiota are protected from major stressors occurring in such desert ecosystems. Therefore, this study focuses on localities where other researchers have observed the existence of islands of habitability [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, the question remains whether these islands are only a location where improved habitable conditions exist or represent actual hotspots of microbial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and results from previous investigators have significantly advanced our current understanding of the composition and behavior of microbial populations in the Atacama Desert [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Biological soil crusts, for example, have been identified as a hotspot of microbial activity and a main driver of nutrient cycling in the less arid regions of the Atacama Desert [ 27 ].…”
Section: Introductionmentioning
confidence: 99%